The measurement by serological means of the impact of the Hong Kong/68 influenza virus on a population Medida sorológica da ação do virus da influenza Hong Kong/68 em uma população - José Alberto N. Candeias; Marguerite S. Pereira (Universidade de São Paulo, 1972)
In order to obtain evidence on the size of the impact of the Hong Kong/68 variant of influenza A2 virus on the population of São Paulo, Brazil, serum samples taken in 1967 before this variant appeared and during successive years after it appeared were examined for their antibody content. Haemagglutination-inhibition tests performed on a total of 2726 serum samples from adults showed a sharp decrease in 1969 of the proportion of sera without antibody to the Hong Kong/68 variant and a corresponding mercase in the proportion with high titres. It was concluded that about three-quarters of the adult population became infected at some time after the variant appeared, the majority in the first year of prevalence. Objetivou-se evidenciar a intensidade da ação da variante Hong Kong/68 do virus da influenza A2 sobre a população de São Paulo, Brasil. Para tanto, foram coletados soros em 1967, antes do aparecimento dessa variante e durante anos seguintes à sua presença, para investigação de seu conteúdo em anticorpos. As provas de inibição da hemaglutinação, levadas a efeito em 2726 amostras de adultos, mostraram acentuada declínio em 1969, relativo à proporção de soros sem anticorpos para Hong Kong/68 e correspondente aumento na proporção com títulos elevados. Conclui-se que cerca de tres quartos da população adulta adquiriu a infecção algum tempo após o aparecimento da variante, a maioria no primeiro ano de prevalência.